Iraqi Criminal Legislation in Addressing the Challenges of Intellectual Extremism and Fighting Terrorism-In Light of the Iraqi Penal Code and the Anti-Terrorism Law - al-Ubaidi, Dr. Musab Thair Abd al-Sattar al-Ubaidi; al-Ubaidi, Prof. Dr. Ahmad Abd al-Sattar Jasim al-Ubaidi (Sulaimani Journal for Humanities, 2026)
The title of our research falls within the third axis of the conference: Islamic Sharia and Legal Legislations: Their Role in Keeping Pace with Contemporary Developments and Addressing Challenges.Given that ideological extremism is one of the most prominent challenges and factors leading to the spread of terrorism, certain individuals or groups within society may exhibit rigid ideological tendencies that often translate into terrorist practices. From this perspective, the importance of adopting effective measures to curb these phenomena, which have become a significant threat to modern societies, becomes evident. Among the most important of these measures is the development of a comprehensive legislative framework through which the state can address the roots of extremism and combat its repercussions that lead to terrorism. In the context of addressing this issue, which is one of the most significant challenges facing Iraqi society, especially after decades of turmoil and crises, it becomes essential to study this phenomenon systematically. Such a study requires an examination of the nature of ideological extremism, its causes, and the factors contributing to its spread. It also necessitates an analysis of the role of noble Islamic legal texts and Iraqi legislative texts in confronting this violent phenomenon, such as the Iraqi Constitution of 2005, the Iraqi Penal Code No. (111) of 1969, as amended, and the Anti-Terrorism Law issued in 2005. The importance of these legislations lies in their being legal tools through which ideological extremism can be confronted. The consequences of extremism in previous years have been severe on both material and social levels, including widespread destruction, aggression against lives and property, and ultimately threatening the security and stability of Iraqi society as a whole.
Keywords: Ideological Extremism; Criminal Legislations; Islamic Sharia; Penal Code